Problematika Pendidikan Akhlak Remaja pada Lingkungan Keluarga Petani di Kenagarian Malampah Pasaman - Melda Leni; Murniyetti Murniyetti (FONDATIA, 2022)
This study contains the problems of adolescent moral education in the farming family environment in the Malampah Pasaman kenagarian. Then it has the purpose of knowing the morals of the child and the efforts of parents to improve the morals of the child. The research was conducted by descriptive qualitative method. With data sources of parents, children, alim ulama, wali nagari, and traditional figures. The data collection techniques used in this study include observation, interviews and documentation in looking for data related to the title of the study that is directly sourced from family or community in Malampah Pasaman. The data analysis techniques used in this study are through the stages of data reduction, data display, and conclution drawing / verification. As a result of this study, the problem of adolescent moral education in the farming family environment in the Malampah Pasaman kenagarian. The conclusion of this article says that children's morals are problematic such as drunkenness, gambling, smoking, promiscuity, disrespect and resistance to parents.